2019
DOI: 10.1111/1365-2435.13424
|View full text |Cite
|
Sign up to set email alerts
|

Floral volatiles structure plant–pollinator interactions in a diverse community across the growing season

Abstract: While the importance of floral odours for pollinator attraction relative to visual cues is increasingly appreciated, how they structure community‐level plant–pollinator interactions is poorly understood. Elucidating the functional roles of flowering plant species with respect to their floral volatile organic compounds (VOCs) and how those roles vary over the growing season is an initial step towards understanding the contribution of floral VOCs to plant–pollinator interaction structure. We sampled the floral V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 67 publications
0
34
0
Order By: Relevance
“…Alternatively, as it occurs with some other invasive plant species (e.g., Miller et al, 2018), the long flowering period in some A. cotula populations might help compete for pollinators that they share with native species. Variation in floral scent VOCs among A. cotula populations also could reflect adaptation to local environmental conditions such as soil moisture (Burkle and Runyon, 2016;Campbell et al, 2019) and the diversity and abundance of local pools of flower visitors (Burkle and Runyon, 2019;Kantsa et al, 2019). Although these patterns in our data could result from local adaptation, climatic and edaphic variables explained only a small proportion (0.013, i.e., 1.3%) of the total variation in phenotypic traits.…”
Section: Trait Variation Among Pnw Populations and Governing Processesmentioning
confidence: 65%
“…Alternatively, as it occurs with some other invasive plant species (e.g., Miller et al, 2018), the long flowering period in some A. cotula populations might help compete for pollinators that they share with native species. Variation in floral scent VOCs among A. cotula populations also could reflect adaptation to local environmental conditions such as soil moisture (Burkle and Runyon, 2016;Campbell et al, 2019) and the diversity and abundance of local pools of flower visitors (Burkle and Runyon, 2019;Kantsa et al, 2019). Although these patterns in our data could result from local adaptation, climatic and edaphic variables explained only a small proportion (0.013, i.e., 1.3%) of the total variation in phenotypic traits.…”
Section: Trait Variation Among Pnw Populations and Governing Processesmentioning
confidence: 65%
“…By modifying plant communities, intensification affects grassland odourscapes, which are assemblages of volatile organic compounds (VOCs) emitted by plants, and in turn alters plant-pollinator interactions [53] and the structure of pollination networks [54]. The only experiment (to the best of our knowledge) that tests this hypothesis [36] found no relationship between botanical composition at the community level after intensification and VOCs.…”
Section: Flower Odoursmentioning
confidence: 93%
“…For example, [36] found a positive correlation between the relative abundance of benzaldehyde and bumblebee species richness and between the relative abundance of butyrolactone and bee species richness. Furthermore, [54], in the Northern Rocky Mountains of the U.S., showed that the richness of bees (standardized by subnetwork size) increased with floral VOC richness and declined with VOC originality.…”
Section: Flower Odoursmentioning
confidence: 99%
“…Studies on plant VOCs have revealed that some VOCs are more frequent than others (Farré-Armengol et al, 2020;Knudsen et al, 2006), but the detailed information structures have not been explicitly studied. To explore the redundancy of plant chemical language and whether the frequency of its vocabulary (VOCs) follows Zipf's law, we gathered the data from the only four community-level plant VOC studies so far, three of which focused on floral VOCs in plant-pollinator networks (Burkle and Runyon, 2019;Filella et al, 2013;Kantsa et al, 2017) and one on leaf VOCs in a plant-herbivore (caterpillar) network (Zu et al, 2020). Additionally, we also use a review study by Farré-Armengol et al 2020(Farré-Armengol et al, 2020, who compiled a floral VOC dataset from 305 species.…”
Section: Zipf 'S Lawmentioning
confidence: 99%
“…From the four community-level plant VOC studies which documented the PV-matrix, three of them (Burkle and Runyon, 2019;Kantsa et al, 2019;Zu et al, 2020) also document insect-plant interaction networks (AP-matrix) in the same community. We found that plant coding patterns vary from community to community (Fig.…”
Section: Coding Decoding and Interactionsmentioning
confidence: 99%